The influence of some technological factors on production obtained from the autumn wheat grown in the system with minimum soil works and the economic efficiency of crop technologies - Mircea Ignea; Felicia Mureşanu; Felicia Cheţan (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
This paper aims to address the problem of achieving autumn wheat production and how technological factors influence the realization of production. It was considered choosing the most efficient technological variants of crop. To this scope we compared, in the experiment, the conventional soil works system (with ploughing, seedbed preparation, fertilizing, seeding) and soil minimum works system or conservative works system. The results led us to conclude that the highest yields are obtained in the conservative system of works, economically feasible yields and that are obtained using a minimum works technology, in which the crop protection is ensured by seed treatment, 2 or 3 treatments per vegetation when productions of 4500-5000 kg / ha are obtained, with reduced expenditures by 9.3 -16.2%, compared to conventional technology.
Keywords: 330; soil minimum works system; conservative agriculture; sustainable agriculture; cultivation technology; autumn wheat